Kajian Perlindungan Hak Pendidikan dan Perlindungan Agama Anak dalam Keluarga Muslim di Kota Medan - Hafsah Hafsah (AHKAM : Jurnal Ilmu Syariah, 2016)
The Study of the Protection of Educational Rights and Protection of Children Religion in Muslim Families in Medan. This article insists that child protection is a mandate. Abandoning children is included as unjust deeds in terms of Islamic law and Law Number 23 Year 2002 on Child Protection. This study aims to describe how parents in Muslim families provide the education right and religious education for their children. Based on the steps of empirical legal research, the writer found that the majority (50%) of Muslim families implemented the protection of the education rights and religious education well, while 30% of them applied less protection and the remaining of 20% did not protect well.DOI: 10.15408/ajis.v16i2.4447